Detecção de co-infecções por Leishmania (l.) chagasi, Trypanosoma evansi, Toxoplasma gondii e Neospora caninum em cães - Coelho, Willian Marinho Dourado [UNESP] (2013)
Co-infections by Leishmania (L.) chagasi, Trypanosoma evansi, Toxoplasma gondii and Neospora caninum in dogs were investigated. Amastigotes forms of Leishmania spp. were detected by cytopathological analysis of lymph nodes in 46,42% (39/84) of dogs. In a male dog, adult, without defined breed, from rural area and positive for Leishmania, were observed flagellated forms of T. evansi in blood smear. By immunofluorescence antibody test, 5,95% (5/84) of dogs were considered reactive to T. gondii, with titer equal to or higher than 1:64, while 3,57% (3/84) were reactive to N. caninum, with titer ≥1:50. Among the animals with visceral leishmaniasis, one showed positive serological response to T. gondii and two for N. caninum. All dogs reactive to N. caninum were from rural area and the predominance of infection by T. gondii was in dogs from urban area. A young male dog from the rural area and seropositive for T. gondii showed Ehrlichia spp. morulae in the cytology and positive reaction for canine distemper virus. Thus, further studies are needed to assess the epidemiology of these infections in canine population, especially with respect to the reservoirs of Trypanosoma spp. in rural areas.